Craft Surrogates - Jonathan Nesci (Oz, 2017)
What “craft” means proves itself to be elusive and, at the same time, ubiquitous regarding the act of making. Through this written exercise I look inward and study where craft is found in my own work as well as observe how it applies to the work of my contemporaries. Although most think of a craftsperson as the individual who makes objects, my interests in fabrication span multiple materials and connection methods. Early in my journey I grew frustrated with limitations of my making skill sets. It took a few years to realize that making wasn’t my strength. Instead, I rely on “craft surrogates” to execute my ideas, people I can rely on for a level of quality that would otherwise take me years to refine.